Chimpanzee Cooperation Is Fast and Independent From Self-Control. (November 2018) - Rosati, Alexandra G.; DiNicola, Lauren M.; Buckholtz, Joshua W.
Large-scale cooperation is a hallmark of our species and appears to be unique among primates. Yet the evolutionary mechanisms that drove the emergence of humanlike patterns of cooperation remain unclear. Studying the cognitive processes underlying cooperative behavior in apes, our closest living relatives, can help identify these mechanisms. Accordingly, we employed a novel test battery to assess the willingness of 40 chimpanzees to donate resources, instrumentally help others, and punish a culpable thief. We found that chimpanzees were faster to make prosocial than selfish choices and that more prosocial individuals made the fastest responses. Further, two measures of self-control did not predict variation in prosocial responding, and individual performance across cooperative tasks did not covary. These results show that chimpanzees and humans share key cognitive processes for cooperation, despite differences in the scope of their cooperative behaviors.